2016
DOI: 10.1039/c6ob01734g
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyfluoro-d-trehalose (FDTre) analogues as potential PET probes for imaging mycobacterial infection

Abstract: Mycobacterium tuberculosis, the etiological agent of human tuberculosis, requires the non-mammalian disaccharide trehalose for growth and virulence. Recently, detectable trehalose analogues have gained attention as probes for studying trehalose metabolism and as potential diagnostic imaging agents for mycobacterial infections. Of particular interest are deoxy-[18F]fluoro-D-trehalose (18F-FDTre) analogues, which have been suggested as possible positron emission tomography (PET) probes for in vivo imaging of M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 61 publications
4
71
0
Order By: Relevance
“…[20] Our group recently demonstrated that [ 19 F]fluorine-modified trehalose (FDTre) analogues can accumulate in the cytoplasm of M. smegmatis via LpqY-SugABC-mediated uptake, which motivates the investigation of [ 18 F]-FDTre radiotracers as M. tuberculosis -selective positron emission tomography (PET) imaging probes. [29] As shown in the present work, it is conceivable that LpqY-SugABC could be similarly exploited to deliver antimicrobial or anti-biofilm cargo to mycobacteria.…”
Section: Resultsmentioning
confidence: 84%
“…[20] Our group recently demonstrated that [ 19 F]fluorine-modified trehalose (FDTre) analogues can accumulate in the cytoplasm of M. smegmatis via LpqY-SugABC-mediated uptake, which motivates the investigation of [ 18 F]-FDTre radiotracers as M. tuberculosis -selective positron emission tomography (PET) imaging probes. [29] As shown in the present work, it is conceivable that LpqY-SugABC could be similarly exploited to deliver antimicrobial or anti-biofilm cargo to mycobacteria.…”
Section: Resultsmentioning
confidence: 84%
“…In addition, 6‐azido trehalose labeling, deployed in conjunction with click chemistry, was used to confirm the function of MmpL3 as the essential TMM flippase and to characterize antitubercular compounds that inhibit it . Fluorine‐modified trehalose analogues can also be metabolized by mycobacteria, a finding which may pave the way for imaging mycobacterial infections in vivo using positron emission tomography (PET) . Recently, a trehalose analogue bearing a solvatochromic moiety was used as a fluorogenic probe for the rapid detection of Mtb in patient sputum samples .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this work established a robust method for the rapid and convenient synthesis of fluorine-modified trehalose analogues, confirmed that the analogues mimic the structure of native trehalose, and demonstrated that they could bind to mycobacteria through a non-mammalian trehalose recycling pathway. Together, the pioneering work of the Barry and Davis groups, 52,115 combined with our contributions, 82,83 should help to pave the way for continued development of trehalose-based PET imaging probes for tuberculosis diagnostics and other applications.…”
Section: Applications Of Trehalose Analoguesmentioning
confidence: 94%
“…In 2016, we reported the use of TreT catalysis to quantitatively convert non-radioactive 19 F-2-FDG ( 6 ) into 19 F-2-FDTre ( 9 ) in a single step in only 15 minutes (Figure 12). 83 The purification steps took 45 minutes, resulting in the production of a concentrated aqueous solution of pure 19 F-2-FDTre in a total of 60 minutes. This timeframe is compatible with the short half-life of 18 F, so the method should be adaptable to the synthesis of 18 F-2-FDTre.…”
Section: Applications Of Trehalose Analoguesmentioning
confidence: 99%